2016
DOI: 10.3390/su8010083
|View full text |Cite
|
Sign up to set email alerts
|

True Green and Sustainable University Campuses? Toward a Clusters Approach

Abstract: Campus greening is often the first step universities take towards sustainability. However, the diffusion of sustainability reporting methodologies and rankings is still at an early stage, and is biased in mainly measuring energy efficiency indicators while omitting basic features enabling meaningful comparisons among centers or addressing social (users) aspects related to long term sustainability transitions. This paper aims to introduce a critical perspective on sustainability university frameworks through: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 31 publications
0
96
0
3
Order By: Relevance
“…Much work has been done on the development of tools to assess sustainability specifically in HEIs, showing the importance of the theme. Several articles have reviewed these tools from different perspectives (e.g., [7,9,14,16,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]). However, it is observed that in these various reviews, the systematization is not homogeneous, noting a lack of common designations and objectives and including tools that do not have as main objective the assessment of the implementation of ESD or are not per se an assessment tool.…”
Section: Sustainability Assessment In Higher Educationmentioning
confidence: 99%
“…Much work has been done on the development of tools to assess sustainability specifically in HEIs, showing the importance of the theme. Several articles have reviewed these tools from different perspectives (e.g., [7,9,14,16,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]). However, it is observed that in these various reviews, the systematization is not homogeneous, noting a lack of common designations and objectives and including tools that do not have as main objective the assessment of the implementation of ESD or are not per se an assessment tool.…”
Section: Sustainability Assessment In Higher Educationmentioning
confidence: 99%
“…The UN, OECD and EU [49][50][51] interventions led to a general convergence of the concept of sustainable development to ensure intergenerational equity, participation and regulatory compliance, and justice [52,53]. In this sense, the university environment is the best place to reflect on education for sustainable development.…”
mentioning
confidence: 99%
“…Many of the parameters needed for time series and cross-country analyses depend on the obtainability of disaggregated data from wide-ranging surveys and cross-section analyses, and there are several critical methodological problems that still impede the creation of such operational indicators of energy efficiency [29]. Regarding specifically the university campus realm, Sonetti et al [30] already argued the lack of a precise analysis based on building types or functions, in one of the most popular green ranking for universities, the UI GreenMetric-World Universities Rankings. The need of three clusters based on urban morphology, climate zones and university functions has been highlighted for sound comparisons among campuses.…”
Section: Motivation and Problem Identificationmentioning
confidence: 99%